(untitled) (De Legibus - Revista de Direito da Universidade Lusófona Lisboa, 2021)
Parody is a genre of artistic expression that has been recognized in the EU as an exception to copyright on the grounds of freedom of expression and the right to criticize. In the case of music videos, where image, music and lyrics are essential, the copying of one of those elements, namely the music, may be justified by the application of the exception. Thus, in this article we will study the parody exception in order to reflect on how the copy is justified and present some arguments in that sense. For this purpose, we will give a brief background of the system of copyright exceptions under EU law, from where we will move on to the analysis of the exception that matters to us. Finally, we will focus on parody in music videos, where we will weave our reflections.